Relapsed and newly diagnosed Graves' disease due to immunization against COVID-19: A case series and review of the literature. Issue 128 (April 2022) - Bostan, Hayri; Ucan, Bekir; Kizilgul, Muhammed; Calapkulu, Murat; Hepsen, Sema; Gul, Umran; Ozturk Unsal, Ilknur; Cakal, Erman
Abstract: In addition to genetic factors, environmental factors such as viruses are thought to be triggers in the development of autoimmune thyroid diseases (AITD) such as Graves' disease (GD). In this context, AITD cases that may be associated with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or immunization have begun to be reported in increasing numbers. Although it is not clear by which pathogenetic mechanisms immunization against coronavirus disease 2019 (COVID-19) triggers the development of AITD, both the potential effect of the adjuvants in the vaccines and the cross-reactivity that can be generated by the molecular similarity of viral particles with mammalian proteins seem to be possible mechanisms. In this article, 7 GD patients consisting of relapsed and newly diagnosed cases following the COVID-19 vaccination were presented. Of these 7 cases, 5 (71.4%) were female, and the median age of the patients was 47 years (range, 31–53). One of the patients was associated with the inactivated COVID-19 vaccine, while the others were associated with the mRNA COVID-19 vaccine. The median post-vaccination symptom onset was 7 days (range, 4–30). Three of the patients had a history of GD and one had a history of Hashimoto's thyroiditis. Rapidly developing Graves' ophthalmopathy was detected in one patient. These cases are cautionary that GD and its extrathyroidal manifestations may develop in a short period after COVID-19 vaccination. When considered together with the literature review, the history of AITD in approximately half of the patients suggests that more attention should be paid to these patients in the post-vaccination period. Nevertheless, multicenter, prospective studies are needed to better understand this possible causal relationship. Highlights: Graves' disease (GD) may develop after SARS-CoV-2 immunization. Graves' ophthalmopathy may occur in a shorter time than expected. GD relapse/conversion could be seen after vaccination in those with a history of autoimmune thyroid disease. Adjuvant effect and/or molecular mimicry are possible pathogenetic mechanisms accused.